(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Information and communication Technology (ICT) has become a valuable, decisive and critical resource for individuals, enterprises, societies and organizations. ICT has reached at every door step, but its use is not fully utilized. University examination system is facing many problems for declaring timely and accurate result. Information and communication Technology (ICT) is a very helpful tool for providing good governance or E-Governance to the community which is bringing a sea-change in the working of organizations and institutions. Students spent their valuable time and money for getting accurate information, but students are not getting desired information. He has to waste his time and money for getting the information by visiting the university, and sometimes he has to give bribe for the same due to several reasons. One of the main reasons is that In most of the Indian Universities, examination system is managed manually. In this paper we propose a framework (with the usage of ICT) for integrated automated examination system to bring speed, reliable, accuracy and transparency in the system. This paper attempts to introduce the concept of ICT for the integration of examination system at the university level to bring reliable, efficient, scalable, transparent and robust e-governance solutions. E- governance can act as a facilitator for equal access of information at different level.